2008
DOI: 10.1111/j.1440-1681.2007.04743.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF POLYPHENOL‐CONTAINING AZUKI BEAN (VIGNA ANGULARIS) EXTRACT ON BLOOD PRESSURE ELEVATION AND MACROPHAGE INFILTRATION IN THE HEART AND KIDNEY OF SPONTANEOUSLY HYPERTENSIVE RATS

Abstract: 1. Hypertension is a major risk factor for myocardial infarction and renal damage, and it has also been shown to have pro-inflammatory actions that increase the formation of reactive oxygen species. Macrophage infiltration has been suggested to play a role in the pathogenesis of hypertension. Azuki beans are known to contain pro-anthocyanidins, a group of polyphenolic bioflavonoids with remarkable radical-scavenging activities in vitro. Therefore, the aim of the present study was to investigate the effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 30 publications
2
27
1
Order By: Relevance
“…Adzuki bean seed coats have been reported to attenuate vascular oxidative stress and inflammation during the progression of hypertension (Mukai & Sato, 2011). Although adzuki bean extracts have been demonstrated to have free radical scavenging activity and to attenuate the elevation blood pressure (Sato et al, 2008), no investigation has been performed on the antioxidant activity of the polysaccharides isolated and purified from the adzuki bean.…”
Section: Introductionmentioning
confidence: 99%
“…Adzuki bean seed coats have been reported to attenuate vascular oxidative stress and inflammation during the progression of hypertension (Mukai & Sato, 2011). Although adzuki bean extracts have been demonstrated to have free radical scavenging activity and to attenuate the elevation blood pressure (Sato et al, 2008), no investigation has been performed on the antioxidant activity of the polysaccharides isolated and purified from the adzuki bean.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, surprisingly, the health benefits provided by lupin polyphenols have been rarely investigated, although these phytochemicals are main bioactive food components, providing numerous health benefits. In particular, they are strong antioxidants, useful for preventing lipid oxidation and atherosclerosis formation, and efficient ACE-inhibitors (Sato, Mukai, Yamate, Kato, Kurasaki, Hatai, et al, 2008;Shahidi & Chandrasekara, 2013;Taku, Umegaki, Sato, Taki, Endoh, & Watanabe, 2007). As already indicated in the introduction, the two most abundant polyphenols in lupin are apigenin-6,8-di-C-β-glucopyranoside H and apigenin 7-O-β-apiofuranosyl-6,8-di-C-β-glucopyranoside I.…”
mentioning
confidence: 99%
“…These results suggest that the extract or the compounds of the plant could be a useful treatment to illnesses related to IL -6 16 . Furthermore, in studies with hypertensive and hyperglycemic animal, it has been observed that this kind of treatment plays an important role in suppressing increases of oxidative stress and macrophage infiltration on kidneys 17 .…”
Section: Discussionmentioning
confidence: 99%